Accidental Pyrethroid Ingestion in Toddler: Near-Fatal Atypical Presentation and Successful Recovery - Pallavidino, Marco; Arango Uribe, Diego; Baskaran, Subashini; Saqib, Aqdas; Elmesserey, Mohamed; Onsy, Ahmed; Fathi, Emad M.; Fink, Christoph; Ramaiah, Anil Kumar H. (Frontiers in Pediatrics, 2020)
We are reporting a case of pyrethroid poisoning with atypical presentation in a 21-month-old toddler who was transferred to us from a peripheral center. Signs and symptoms at presentation were predominantly of cardiopulmonary dysfunction contrary to more common presenting features of gastrointestinal and neurological impairment. The reason for this seems to be the aspiration pneumonitis as a consequence of vomiting induced at home, rather than the toxin itself even though a rather rapid progression of lung injury does not rule out the possibility. He had developed decreased level of consciousness and increased work of breathing after ingestion, which had progressed to Acute Respiratory Distress Syndrome, septic shock and multi organ failure. He even had a brief cardiac arrest with Return of Spontaneous Circulation after 5 minutes of cardiopulmonary resuscitation, immediately after arrival at our unit, which seemed more likely to be a consequence of inappropriate management during transfer of the child. In addition to antibiotics and vasopressors, he required high frequency oscillatory ventilation and prone positioning and lung-protective conventional ventilation. His cardiopulmonary status improved gradually and he was successfully extubated after 12 days. Other organ systems also showed complete recovery. Even though Magnetic Resonance Imaging of brain showed features suggestive of hypoxic-ischemic encephalopathy he showed complete neurological recovery. He was thriving well at three-month follow-up without neurological deficits and normal renal and liver function. Atypical presentation of pyrethroid poisoning is associated with significant morbidities and there seems to no reliable parameters in children to identify the risk of the same. Considering that there is no specific antidote, prompt and aggressive supportive therapy is necessary for a favourable outcome. This case highlights several important aspects: first, attempt to induce emesis, especially outside of a healthcare facility is not only ineffective but also highly dangerous, and should not be done; second, unstable patients require inter and intrahospital transfer by experienced and trained personnel; and lastly, management for these complex cases should be done as early as possible in a center which is equipped to provide high level of circulatory and ventilatory support while prioritising neuro-protective measures, and neurologic recovery and rehabilitation